A FEMINIST-STYLISTIC ANALYSIS IN WOMAN AT POINT ZERO NOVELS - Sinulingga, Amsaldi Wahyu Kristian; Yurilsya, M.; Siddiq, M. Barru (Universitas Katolik Santo Thomas Medan, 2020)
This study describes the feminist stylistics in Woman at Point Zero novel. Woman at Point Zero is a novel about feminism, woman that demand equality and justice. The methods used is descriptive qualitative. The objective of this study is to find out the word, phrase / sentence, and discourse level presented in gender-specific in Woman at Point Zero novel. The result of this study uncovered the writing style or practice of the said author that has to do with the presentation of gender. Female characters differ from the male in that there are more descriptions given to them which pertain to their thoughts, emotions, experiences, vulnerability towards men, and their physical characteristics. Males, on the other hand, are described according to their physical strength, personalities, attitudes, which dominate females. The novel contains descriptions of women and men focusing on their physique, some of which displaying sensual appeal.